Impact of multiple aerial spraying of Bacillus thuringiensis on bagworm control in oil palm smallholdings in Johor, Malaysia - Nur Robaatul Adhawiyah Mohd Ali Napiah; Noorhazwani Kamarudin; Mohd Fahmi Keni; Mohd Najib Ahmad; Mohamed Mazmira Mohd Masri (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The outbreak of bagworm has been a severe threat, causing significant loss to the oil palm industry in Johor, Malaysia. This study investigated the impact of multiple aerial applications of Bacillus thuringiensis (Bt)-based biopesticides in controlling the bagworm outbreak at two smallholdings in Johor, namely Smallholding A (Sh.A) and Smallholding B (Sh.B). Two types of agricultural aircrafts used in this study were Grumman G-164 A Super AgCat and M-18 Dromader. The results showed that a significant reduction of bagworms (83.5%) was recorded after the third round of aerial spray in Sh.A. Whilst, Sh.B recorded a significant reduction of bagworms (83.5%) after the fourth round of aerial spray. The result indicated that multiple applications of Bt aerial spray at the precise timing and strategy based on the bagworm’s life cycle are crucial in ensuring the application’s effectiveness in bringing down the bagworm population to below the economic threshold level (ETL). A census conducted in 2019 and 2020 recorded that the bagworm population in both areas maintained below the threshold level even after more than three years of application. With the implementation of a long-term Integrated Pest Management (IPM) strategy, such as planting beneficial plants, the bagworm population can be maintained under ETL even after years of aerial sprays.